Mechanism of enhanced freshness formulation in optimizing antioxidant retention of gold kiwifruit (Actinidia chinensis) harvested at two maturity stages - Mthembu, Sisanda S. L.; Magwaza, Lembe S.; Tesfay, Samson Z.; Mditshwa, Asanda (Frontiers in Sustainable Food Systems, 2023)
Kiwifruit exhibits a climacteric ripening pattern and has as an extremely perishable nature. Considering that high perishability leads to a loss in antioxidants and overall nutritional quality. This study aimed to examine the efficacy of enhanced freshness formulation (EFF), a hexanal-based formulation containing antioxidants such as geraniol, α-tocopherol and ascorbic acid, on maintaining the bioactive compounds of gold kiwifruit (cv. ‘Y368’) harvested at two maturity stages. Kiwifruits were treated with three treatments, namely, control (untreated fruit), 0.01 and 0.02% (v/v) EFF. Fruits were treated with 8 weeks of cold storage at 0°C and 90% relative humidity, then transferred to 20°C for 8 days. Three bioactive compounds (ascorbic acid, total phenolics and flavonoids), antioxidant capacities using DPPH and FRAP assays, polyphenol oxidase, ascorbate oxidase, phenylalanine and tyrosine ammonia lyase enzyme activities were evaluated. The results showed that EFF significantly (p < 0.05) influenced bioactive compounds, antioxidant capacities and the activity of enzymes involved in the synthesis and oxidation of bioactive compounds. The maturity stage significantly influenced the content of bioactive compounds. Later harvested kiwifruit had greater content of bioactive compounds, compared to earlier harvested kiwifruit. The total phenolic content was 0.77, 1.09 and 1.22 mg GAE g−1 FW for control, 0.01 and 0.02% EFF, respectively. The FRAP antioxidant concentration was 0.76, 0.91 and 0.96 μmol Fe (II) g−1 FW for control, 0.01 and 0.02% EFF. The findings illustrate the capacity of EFF to optimize bioactive compounds and storability of kiwifruit during postharvest storage.